Możliwości wykorzystania biblioterapii w stymulowaniu rozwoju emocjonalnego starszych dzieci w przedszkolu = Possible use of bibliotherapy in stimulating emotional development of older children in kindergarten - Pasterniak-Kobyłecka, Ewa (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Owing to their cognitive, educational, aesthetic and therapeutic functions literary texts can support the development of the individual`s emotional intelligence. Literature stimulates imagination, lets children gain new experiences, helps them to understand themselves, other people and the world around them.
Keywords: emocje; rozwój; inteligencja emocjonalna; biblioterapia; bibliotherapy; development; emotions; emotional intelligence